Mesoscale Forecasts of Stratospheric Mountain Waves - Dörnbrack, Andreas; Leutbecher, Martin; Volkert, Hans; Wirth, Martin (Wiley, 1998)
A forecasting system was set up to infer the impact of mountain waves for producing mesoscale temperature anomalies in the stratosphere. It was successfully applied during a recent aircraft campaign which operated out of Rovaniemi, northern Finland, between 18 December 1996 and 15 January 1997. The forecast information led to the successful detection of mountain-induced polar stratospheric clouds on 9 January 1997. For this event mesoscale forecasts, hindcast runs including grid nesting and comparisons with lidar observations and radiosonde measurements are presented.